Importance of Individual Germination Receptor Subunits in the Cooperative Function between GerA and Ynd - Aspholm, Marina (J Bacteriol, 2019)
Germination of Bacillus spores is triggered by the binding of specific nutrients to germinant receptors (GRs) located in the spore’s inner membrane. The GRs typically consist of A, B, and C subunits, encoded by tricistronic ger operons. The Bacillus licheniformis genome contains the gerA family operons gerA, ynd, and gerK. In contrast to the ABC(D) organization that characterizes gerA operons of many Bacillus species, B. licheniformis genomes contain a pentacistronic ynd operon comprising the yndD, yndE(3), yndE(2), yndF(1), and yndE(1) genes encoding A, B, B, C, and B GR subunits, respectively (subscripts indicate paralogs). Here we show that B. licheniformis spores can germinate in the absence of the Ynd and GerK GRs, although cooperation between all three GRs is required for optimal germination with amino acids. Spores carrying an incomplete set of Ynd B subunits demonstrated reduced germination efficiencies, while depletion of all three Ynd B subunits restored germination of the spore population to levels only slightly lower than those of wild-type spores at high germinant concentrations. This suggests that the presence of an incomplete set of Ynd B subunits exhibits a dominant negative effect on germination and that the A and C subunits of the Ynd GR are sufficient for the cooperative functionality between Ynd and GerA. In contrast to the B subunits of Ynd, the B subunit of GerA was essential for amino acid-induced germination. This study provides novel insights into the role of individual GR subunits in the cooperative interaction between GRs in triggering spore germination. IMPORTANCE Spore-forming bacteria are problematic for the food industry, as spores can survive decontamination procedures and subsequently revive in food products, with the risk of food spoilage and foodborne disease. The Ynd and GerA germination receptors (GRs) cooperate in triggering efficient germination of Bacillus licheniformis spores when nutrients are present in the surrounding environment. This study shows that the single B subunit of GerA is essential for the cooperative function between Ynd and GerA, while the three B subunits of the Ynd GR are dispensable. The ability of GRs lacking individual subunits to stimulate germination together with other GRs could explain why ger operons lacking GR subunit genes are maintained in genomes of spore-forming species.